2015
DOI: 10.1002/mrm.25757
|View full text |Cite
|
Sign up to set email alerts
|

Removing silicone artifacts in diffusion-weighted breast MRI by means of shift-resolved spatiotemporally encoding

Abstract: # These authors contributed equally to this work. AbstractPurpose-Evaluate the usefulness of diffusion-weighted spatiotemporally-encoded (SPEN) methods to obtain ADC maps of fibroglandular human breast tissue, in the presence of silicone implants.Methods-Seven healthy volunteers with breast augmentation were scanned at 3T using customized SPEN sequences yielding separate silicone and water 1 H images in one scan, together with their corresponding diffusion-weightings.Results-SPEN's ability to deliver multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…SPEN is a single‐shot imaging modality that can also be extended to multishot interleaved operation with certain benefits in the ensuing spatial resolution and sensitivity. SPEN relies on performing a consecutive excitation or refocusing of the spins, achieved by applying a linearly chirped radio frequency (RF) pulse acting in the presence of an encoding gradient G e . In the multislice, fully refocused pulse sequence here assayed (Figure ), spins are first excited by a slice‐selective 90° pulse and then acted upon by a swept 180° inversion pulse, linearly chirping over a bandwidth BW during a time T e while in the presence of a y ‐axis G e gradient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPEN is a single‐shot imaging modality that can also be extended to multishot interleaved operation with certain benefits in the ensuing spatial resolution and sensitivity. SPEN relies on performing a consecutive excitation or refocusing of the spins, achieved by applying a linearly chirped radio frequency (RF) pulse acting in the presence of an encoding gradient G e . In the multislice, fully refocused pulse sequence here assayed (Figure ), spins are first excited by a slice‐selective 90° pulse and then acted upon by a swept 180° inversion pulse, linearly chirping over a bandwidth BW during a time T e while in the presence of a y ‐axis G e gradient.…”
Section: Methodsmentioning
confidence: 99%
“…Additional resolution improvements can result from SPEN’s built‐in ability to restrict the targeted FOVs. Single‐shot studies incorporating SPEN into diffusion schemes have shown this method’s potential for overcoming SE EPI’s characteristic limitations in animals and humans . The purpose of the study is to explore SPEN’s ability to deliver quantitative diffusion breast maps at sub‐millimeter in‐plane resolutions, in clinically relevant situations.…”
Section: Introductionmentioning
confidence: 99%
“…These include multi-shot schemes liable to motion-derived errors, as well as single-shot acquisitions based on radial samplings or on the use of multiple rf-driven spin echoes 15 19 . Recently introduced single-shot 2D SPEN methods can achieve many of these goals 20 , 35 , 45 47 , yet if overwhelmed by inhomogeneities even these methods are liable to yield corrupted images reflecting ΔB o displacements. xSPEN by contrast shows unprecedented resilience to in-plane field inhomogeneities, with the sole distortions identified in their single-scan 2D images arising from limitations in the slice selection process 31 .…”
Section: Discussionmentioning
confidence: 99%
“…35,[44][45][46], yet if overwhelmed by inhomogeneities even these methods are liable to yield corrupted images reflecting ΔB o displacements. xSPEN by contrast shows unprecedented resilience to in-plane field inhomogeneities, with the sole distortions identified in their singlescan 2D images arising from limitations in the slice selection process(30).…”
mentioning
confidence: 99%
“…Homonuclear single-scan 2D correlations relying on enhancements derived from para-hydrogen have also been implemented 120 . Single-scan 2D spectral-spatial correlations have also been demonstrated in this manner, including in hyperpolarized and thermal preclinical, as well as in clinical human MRI settings [121][122][123][124][125] . As mentioned, the spatial extent of a homogeneous sample can also be used to encode other sorts of information besides chemical shifts of evolving spins.…”
Section: Applications Of Single-scan Nd Nmrmentioning
confidence: 90%